Biofunctional Nanodot Arrays in Living Cells Uncover Synergistic Co‐Condensation of Wnt Signalodroplets. Issue 50 (20th October 2022) - Philippi, Michael; Richter, Christian P.; Kappen, Marie; Watrinet, Isabelle; Miao, Yi; Runge, Mercedes; Jorde, Lara; Korneev, Sergej; Holtmannspötter, Michael; Kurre, Rainer; Holthuis, Joost C. M.; Garcia, K. Christopher; et al.
Abstract: Qualitative and quantitative analysis of transient signaling platforms in the plasma membrane has remained a key experimental challenge. Here, biofunctional nanodot arrays (bNDAs) are developed to spatially control dimerization and clustering of cell surface receptors at the nanoscale. High‐contrast bNDAs with spot diameters of ≈300 nm are obtained by capillary nanostamping of bovine serum albumin bioconjugates, which are subsequently biofunctionalized by reaction with tandem anti‐green fluorescence protein (GFP) clamp fusions. Spatially controlled assembly of active Wnt signalosomes is achieved at the nanoscale in the plasma membrane of live cells by capturing the co‐receptor Lrp6 into bNDAs via an extracellular GFP tag. Strikingly, co‐recruitment is observed of co‐receptor Frizzled‐8 as well as the cytosolic scaffold proteins Axin‐1 and Disheveled‐2 into Lrp6 nanodots in the absence of ligand. Density variation and the high dynamics of effector proteins uncover highly cooperative liquid–liquid phase separation (LLPS)‐driven assembly of Wnt "signalodroplets" at the plasma membrane, pinpointing the synergistic effects of LLPS for Wnt signaling amplification. These insights highlight the potential of bNDAs for systematically interrogating nanoscale signaling platforms and condensation at the plasma membrane of live cells. Abstract : High‐density arrays of biofunctionalized nanodots with diameters of 300 nm enable spatially controlled assembly of active Wnt signaling platforms in the plasma membrane. Massive parallelization at the single cell level uncovers receptor density‐dependent co‐condensation of cytosolic effector proteins, suggesting digitalized transmembrane signaling controlled by liquid–liquid phase separation.